5PSQ-202 Biosimilars in the real world: results from an active pharmacovigilance programme in a Portuguese oncology hospital. (14th March 2021) - Rigueiro, G; Mendes, D; Abrantes, J; Pais, AF; Penedones, A; Alves, C; Batel-Marques, F
Abstract : Background and importance: The use of biologics is essential in the management of several types of cancer. When patents of reference biologics expired, biosimilars emerged, widening the patient's access to biological therapy and providing cost savings to healthcare systems. The hospital pharmacist stands in a privileged position, structuring post-marketing surveillance and implementing active pharmacovigilance programmes to monitor the safety of these technologies. Aim and objectives: The aim of this study was to evaluate the safety profiles of two biosimilar medicines (rituximab and trastuzumab) in the treatment of cancer patients within a Portuguese oncology hospital using an intensive monitoring programme. Material and methods: This hospital based prospective observational study followed a cohort event monitoring approach focused on signalling suspected adverse drug reactions (ADRs). Patients undergoing treatment with rituximab biosimilar CT-P10 (Truxima) or trastuzumab biosimilar CT-P6 (Herzuma) were recruited over an 11 month and a 6 month period (from 1 November 2018 and 1 April 2019, respectively, until 30 November 2019). A paper based ADR reporting form was developed for each biosimilar medicine and completed by clinicians. Clinical secretariats sent the reports through an electronic platform to the pharmacovigilance department for analysis of seriousness, expectedness and causality of suspected ADRs. Results: 94 patients received biosimilar medicines (rituximab, n=35; trastuzumab, n=59). Of these, 4 (11.4%) experienced 16 ADRs with rituximab and 1 patient (1.7%) experienced 5 ADRs with trastuzumab. All case reports contained serious and expected ADRs that were at least probably related to the biosimilar medicines under study. Based on the MedDRA PT coding, the most reported ADR for rituximab CT-P10 (Truxima) was chest discomfort (n=4; 19.1%), followed by odynophagia (n=2; 9.5%). Trastuzumab CT-P6 (Herzuma) was associated with back pain, headache, pain in extremity, tachypnoea and tremor (each, n=1; 4.8%). Conclusion and relevance: The results of this study suggest that in the real world setting, the biosimilar rituximab and biosimilar trastuzumab to treat cancer patients were associated with acceptable safety profiles. No new safety problems were identified. Also, the results of this study showed that carrying out active pharmacovigilance programmes in oncology pharmacy practice is feasible and that such activities contribute to better characterisation of the safety profiles of medicines. References and/or acknowledgements: Conflict of interest: No conflict of interest